واقع تدريب وتأهيل المورد البشري في المؤسسات الرياضية - دراسة ميدانية بمديرية الشباب والرياضة برج بوعريريج - بن صفية, طه; د.نويري, بوبكر (معهد علوم وتقنيات النشاطات البدنية والرياضية بالمسيلة, 2023)
تهدف هذه الدراسة إلى الوقوف على واقع تدريب وتأهيل المورد البشري في المؤسسات الرياضية وقد اخترنا مديرية الشباب والرياضة برج بوعريريج لتكون محل دراسة، حيث قمنا من خلال هذه الدراسة بمعالجة إشكالية الموضوع المتمثلة في: ''هل هناك تدريب وتأهيل للمورد البشري في المؤسسة الرياضية؟'' اعتمدنا في دراستنا على المنهج الوصفي التحليلي وقد تمثلت الأداة التي استعملناها في الاستبيان الذي تم توزيعه على أفراد العينة المتمثلة في20 إداري ومسير في مديرية الشباب والرياضية برج بوعريريج بعد استبعاد أفراد العينة الاستطلاعية والمقدر عددهم ب 5 أفراد. كشفت لنا هذه الدراسة أن المؤسسة الرياضية تهتم بتدريب وتأهيل المورد البشري من خلال توفير الإمكانات اللازمة لنجاح العملية التدريبية وكذا الحرص على وضع برامج تدريبية فعالة إلا أنه فيه بعض المعيقات التي تعرقل نجاح العملية التدريبية يجب على المؤسسة الرياضية تجنبها والعمل على عدم وقوعها في المستقبل. الكلمات المفتاحية: تدريب ، تأهيل ، المورد البشري ، المؤسسة الرياضية. Abstract This study aims to stand on the reality of training and qualifying the human resource in sports’ institution . Accordingly , we have chosen ‘Sport and youth Directorate’ of Bordj Bou Arreridj to be under consideration. The purpose of our study was to answer our research question “Is there training and qualification for the human resource in sports institutions? A descriptive analytical approach was employed where a questionnaire was administered to our sample of study; being consisted of 20 administrators and managers in “Sport and youth Directorate” in Bordj Bou Arreridj after excluding the exploratory sample estimated at 05 individuals. The study revealed that the sports’ institution is interested in training and qualifying the human resource by providing all necessary means to ensure the success of the training process as well as ensuring the development of effective training. However, the sports’ institution must avoid some constraints which hinder the training process. Key words: training, qualifying, human resource, sports institution.
Keywords: تدريب وتأهيل المورد البشري في المؤسسات الرياضية; تدريب وتأهيل المورد البشري; المورد البشري